Building Environmental Awareness through Communication in the Coastal Areas of Batahan Subdistrict, Mandailing Natal, North Sumatra - Nurfitriani M Siregar; Gina Sonya Pane; Mhd Alwi Ritonga; Iqbal Hakim Hasibuan; Ahmad Riski Sulaiman Nasution (CV. AFDIFAL MAJU BERKAH, 2025)
Environmental awareness among coastal communities in Batahan District still faces various challenges, particularly those related to waste management, coastal ecosystem degradation, and low levels of environmental literacy. These issues are compounded by the limited availability of waste processing facilities, the lack of continuous environmental education, and the persistent habit of littering found in several coastal areas. Responding to these concerns, the Islamic Communication and Broadcasting Study Program carried out a community service initiative focused on fostering environmental awareness through participatory, dialogic, and educational communication approaches. This community engagement activity was designed using a qualitative research method to explore the community’s needs and identify the most effective communication patterns. The program included educational sessions on the importance of preserving coastal ecosystems, ecological campaigns disseminated through local social media platforms, and direct assistance to coastal community groups in developing relevant environmental programs. This approach not only emphasized the delivery of information but also encouraged active involvement of community members at every stage, making the educational process more meaningful and easily accepted. The results of the activity indicate a significant increase in community understanding regarding the importance of preserving coastal environments, including awareness of the dangers of plastic waste and harmful fishing practices. Community participation in coastal clean-up activities also improved, marked by the establishment of village-level environmental awareness groups. This initiative demonstrates that effective communication, particularly interpersonal and group communication, plays a crucial role in encouraging sustainable ecological behavior change within coastal communities